Retinopathy of prematurity and placental histopathology findings: A retrospective cohort study - Sam Ebenezer Athikarisamy; Sam Ebenezer Athikarisamy; Geoffrey C. Lam; Geoffrey C. Lam; Matthew N. Cooper; Tobias Strunk; Tobias Strunk; Tobias Strunk (Frontiers Media S.A., 2023)
AimRetinopathy of prematurity (ROP) is a biphasic vaso-proliferative disease that has the potential to cause blindness. In addition to prematurity and hyperoxia, perinatal infection and inflammation have been reported to play a critical role in the pathogenesis of ROP. The aim of this study was to assess the association between placental inflammation and the severity of ROP.MethodsA retrospective study of infants (<30 weeks of gestational age) born at the King Edward Memorial Hospital, a tertiary perinatal center in Western Australia.ResultsA total of 878 infants were included in this study (ROP stage 0-2 = 829; 3 or more = 49). The presence of maternal chorioamnionitis appeared to show signs of an association with reduced odds of severe ROP: mild chorioamnionitis OR=0.43 (95% CI: 0.17, 1.05) and severe chorioamnionitis OR=0.68 (95% CI: 0.29, 1.60). A strong association was observed for oxygen supplementation at 36 weeks (OR: 5.16; p < 0.001), exposure to postnatal steroids (OR: 6.65; p < 0.001), and receipt of platelet transfusion (OR: 8.21; p < 0.001).ConclusionMaternal chorioamnionitis or fetal chorioamnionitis was associated with reduced odds of severe ROP. A strong association was found in infants who needed oxygen supplementation at 36 weeks and those who required steroids or platelets in the postnatal period.